Efficacy of ultraviolet radiation as non-thermal treatment for the inactivation of Salmonella typhimurium TISTR 292 in pineapple fruit juice - Mansor, Atikah; Shamsudin, Rosnah; Mohd Adzahan, Noranizan; Hamidon, Mohd Nizar (Elsevier, 2014)
The purpose of this study was to investigate the efficacy of UV-C treatment with the Dean Vortex technology to inactivate the presence of Salmonella typhimurium TISTR 292 in pineapple juice at three different frequencies (30, 35 and 40 Hz). The increasing of pump frequency was resulted an increasing of flow rates. The UV dosage was measured for 30, 35 and 40 Hz which are 13.75, 10.37 and 10.10 mJ/cm2, respectively. The microbial counts of Salmonella typhimurium decreased with increasing UV-C dosage. Highest microbial reduction was achieved at pump frequency of 30 Hz (dosage 13.75 mJ/cm2) with reduction of 5-log10 CFU/ml.